ANALISIS MATERI PEMBELAJARAN BAHASA JERMAN PADA BUKU DEUTSCH IST EINFACH KELAS XII UNTUK KETERAMPILAN MEMBACA - Sholiha, Farah; Pujosusanto, Ari (LATERNE, 2021)
The teacher needs learning materials to conduct the teaching-learning process. Learning materials are all kinds of materials used by the teachers which contain learning materials to achieve the learning objectives. There are lots of learning material sources. There are many learning material sources besides books like the internet in recent days. Deutsch ist einfach is one of the books that can be used as a learning source. The teacher is not allowed to deliver learning materials randomly. The learning materials must adapt to the applicable curriculum, which is curriculum 2013. Based on the analysis above, we need an analysis to know whether the learning materials are applicable to the curriculum in 2013. The students must possess four skills such as reading, writing, speaking, and listening. Reading is a very important basic skill to be learned. The problem formulation in this research is How is the material suitability in the book Deutsch ist einfach grade XII for reading skills with the curriculum in 2013? This scientific article aims to know the material suitability in the book Deutsch ist einfach grade XII for reading skills with the curriculum in 2013. The problem limitation used in this scientific article is analyzing the theme of Hobby. This scientific article uses a qualitative approach with a literature study approach. The data source in this research is the book Deutsch ist einfach Grade XII. The data used in this research is a learning material in the form of descriptive text related to the theme of Hobby. The data will be analyzed after it is found. There are three aspects used to measure the material suitability with curriculum in 2013. They are the Wortschatz used, linguistic structure in accordance with the syllabus for Grade XII, and also the Redemittel used. After completing the text analysis process, six descriptive texts that are in accordance with the curriculum in 2013 will be found. The analyzed texts which are in accordance with the curriculum in 2013 will be used as the learning materials for learning German in the form of reading competence.